Oral Mucoceles in Children—Analysis of 56 New Cases. Issue 5 (6th April 2015) - Bodner, Lipa; Manor, Esther; Joshua, Ben‐Zion; Shaco‐Levy, Ruthy
Abstract Background Mucoceles are common cystic lesions of the oral mucosa. Extravasation mucoceles (EMs) are mainly found in the lower lip of young patients, whereas retention mucoceles (RMs) are usually located in the cheek or palate of older patients. This study was undertaken to more fully characterize the clinicopathologic features of mucoceles in pediatric patients. Methods The records of 56 pediatric patients with mucoceles were included in the study. Age, sex, history of trauma, intraoral site, size, and method of treatment were evaluated. Histopathologically the lesions were classified as being EMs or RMs. Results The age range was 1.5 to 16 years (mean age 11.2 yrs). Of the 56 patients, 24 (43%) were males and 32 (57%) were females, with a male:female ratio of 1:1.33. A history of trauma was recorded in 32 (57%) patients of the lower lip. The intraoral sites were the lower lip (38 [68%]), tongue (10 [18%]), and floor of the mouth (8 [14%]). Of the 56 patients, 44 (79%) were EM and 12 (21%) were ranulas. No RMs were found. Mucoceles ranged from 0.3 to 3.8 cm in diameter (mean 0.9 cm). The treatment of EMs was surgical excision. Cryosurgey, electrosurgery, and carbon dioxide laser were also used. Conclusion In contrast to adults, where EM and RM types can be found, among children all cases are of the EM type. The disparate site and age incidences of EMs and RMs of the oral mucosa suggest that these two types are not related and possibly have a different etiopathogenesis.